Pengaruh Inovasi Produk dan Citra Merek terhadap Minat Beli pada Produk Teknologi di Indonesia - Nurmayani Nurmayani; Nurul Halisya; Isra Rafika Sihombing (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2026)
Rapid technological development and increasingly intense market competition in Indonesia have made product innovation and brand image important factors in shaping consumers' purchase intention toward technological products, such as smartphones and other digital devices. This study aims to analyze the influence of product innovation and brand image on consumers' purchase intention for technological products in Indonesia. The study employed a qualitative approach through library research, with data collected from various national and international journals accessed through Google Scholar, Semantic Scholar, and SINTA, supported by relevant books. The synthesis of previous studies indicates that product innovation through feature development, design improvement, and value enhancement has a positive and significant effect on consumers' purchase intention. Likewise, brand image, which includes perception, trust, prestige, and reputation, also has a positive and significant influence, both partially and simultaneously. These findings are consistent with Kotler and Keller's consumer behavior theory and provide strategic implications for technology companies to continuously innovate and build strong brand equity.